Risks of and from SARS-CoV-2 infection and COVID-19 in people with diabetes: a systematic review of reviews - Hartmann-Boyce, J; Rees, K; Perring, JC; Kerneis, SA; Morris, EM; Goyder, C; Otunla, AA; James, OA; Syam, NR; Seidu, S; Khunti, K (American Diabetes Association, 2021)
Background: This review was commissioned by the World Health Organization and presents a summary of the latest research evidence on the impact of coronavirus disease 2019 (COVID-19) on people with diabetes (PWD).